Enhancing concrete performance with Jordanian natural zeolite for continuous reinforced pavements construction and design - Ata, Tamara Bani; Ibraheem, Asmaa T. (Al-Nahrain Journal for Engineering Sciences, 2026)
Real-life strategies are applied to assess pavement functionality, high-quality performance, and durability throughout its service life. Estimating pavement maintenance and sustainability is difficult. High-performance continuous reinforced concrete pavement (CRCP) structural design and Jordanian natural zeolite (JNZ) as a sustainable supplementary cementitious material (SCM) and unique mixed cement for green manufacturing are researched in this paper. The results obtained from this study showed that replacing cement with JNZ powder at 0%, 10%, 15%, and 20% improved concrete performance. Natural zeolite-mixed cement preserved concrete quality and reduced the need for ordinary Portland cement (OPC) and sulfate-resistant cement (SRC) clinker. After that, slab universal testing equipment and Jordanian zeolite-blended cement-reinforced concrete slabs were developed for CRCP performance. Therefore, fresh concrete was tested for partial cement substitution and standard mixture workability. Compressive, tensile, and flexural strength tests on 7 and 28 days and durability test (water absorption) were utilized to assess concrete strength and natural zeolite’s potential to reduce resource consumption and carbon footprint while maintaining structural integrity using Open LCA. Sustainable CRCP structure development improved performance, resource conservation, and carbon footprint over the prior mix, according to EIA (Environmental Impact Assessment) software and chemical tests. This research improves materials and supports global sustainability goals.